Author Correction: Equation of state of iron under core conditions of large rocky exoplanets. (July 2018) - Smith, Raymond; Fratanduono, Dayne; Braun, David; Duffy, Thomas; Wicks, June; Celliers, Peter; Ali, Suzanne; Fernandez-Pañella, Amalia; Kraus, Richard; Swift, Damian; Collins, Gilbert; Eggert, Jon
In the version of this Letter originally published, in the Acknowledgements, the surname of M. Herrmann was misspelt as 'Hermann'. This has now been corrected.